2019
DOI: 10.1186/s12978-019-0739-0
|View full text |Cite
|
Sign up to set email alerts
|

Community health worker promotions increase uptake of long-acting reversible contraception in Rwanda

Abstract: Background We coordinated community health worker (CHW) promotions with training and support of government clinic nurses to increase uptake of long-acting reversible contraception (LARC), specifically the copper intrauterine device (IUD) and the hormonal implant, in Kigali, Rwanda. Methods From August 2015 to September 2016, CHW provided fertility goal-based family planning counseling focused on LARC methods, engaged couples in family planning counseling, and provided w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 46 publications
1
26
1
Order By: Relevance
“…[38][39][40] We hypothesized that provider training would be associated with LARC uptake, since other studies in SSA have found providers to be a barrier based on biases based on sociodemographics, misconceptions about safety or lack of training in provision. 41 However, we did not find a significant association between provider training and LARC uptake, which could be due to several reasons. The indicator measured whether a provider received inservice training in the last two years, but did not account for how recently the training took place or the quality of that training.…”
Section: Discussioncontrasting
confidence: 58%
“…[38][39][40] We hypothesized that provider training would be associated with LARC uptake, since other studies in SSA have found providers to be a barrier based on biases based on sociodemographics, misconceptions about safety or lack of training in provision. 41 However, we did not find a significant association between provider training and LARC uptake, which could be due to several reasons. The indicator measured whether a provider received inservice training in the last two years, but did not account for how recently the training took place or the quality of that training.…”
Section: Discussioncontrasting
confidence: 58%
“…We hypothesize that even only less than one in ten of women discussed family planning with CHWs their odds was higher, if there was an opportunity for all women to discuss family planning with CHWs, the coverage would have been much higher. This implies that more efforts should also be invested in community based interventions to reach communities with appropriate information to increase family planning uptake (55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, IUDs and implants were used by only less than 10% of women in reproductive age. Gallo, 2019;Austad, Shah, & Rohloff, 2018;Bhandari, Pokhrel, Gabrielle, & Amatya, 2019;Dempsey, Billingsley, Savage, & Korte, 2012;Finer, Jerman, & Kavanaugh, 2012;Harzif, Mariana, Malik, Silvia, & Lovita, 2019;Weber, Briggs, & Hanson, 2017), parity (Asad et al, 2019;Bhandari et al, 2019;Finer et al, 2012;Mazzei et al, 2019), family welfare (Adedini et al, 2019;Bhandari et al, 2019;Fekadu, Omigbodun, Roberts, & Yalew, 2019), women's knowledge (Dempsey et al, 2012;Harzif et al, 2019;Mazzei et al, 2019), women's education (Adedini et al, 2019;Asad et al, 2019;Mazzei et al, 2019;Ontiri et al, 2019;Secura & McNicholas, 2013), husband education (Bhandari et al, 2019), women's occupation (Adedini et al, 2019;Fekadu et al, 2019), husband's occupation (Bhandari et al, 2019), religion (Mazzei et al, 2019;Ontiri et al, 2019), desire for children in the future (Bhandari et al, 2019;Ontiri et al, 2019), accessibility (Secura & McNicholas, 2013) were documented as significant predictors of LARC used. Health related factors for LARC adoption were health workers skills (Harzif et al, 2019;Ontiri et al, 2019), counselling (Mazzei et al, 2019;Secura & McNicholas, 2013) and history of abortion (Fekadu et al, 2019)…”
Section: Introductionmentioning
confidence: 95%
“…Health related factors for LARC adoption were health workers skills (Harzif et al, 2019;Ontiri et al, 2019), counselling (Mazzei et al, 2019;Secura & McNicholas, 2013) and history of abortion (Fekadu et al, 2019). Other factors such as cost of contraception (Adedini et al, 2019;Finer et al, 2012;Harzif et al, 2019;Secura & McNicholas, 2013), health worker training on LARC (Mazzei et al, 2019;Secura & McNicholas, 2013), logistical support (Mazzei et al, 2019;Secura & McNicholas, 2013), partner's support (Mazzei et al, 2019), myths (Secura & McNicholas, 2013) and exposure to mass media (Adedini et al, 2019) were also related to the used of LARC.…”
Section: Introductionmentioning
confidence: 99%